2001
DOI: 10.2165/00019053-200119120-00004
|View full text |Cite
|
Sign up to set email alerts
|

Direct Costs of Schizophrenia in Italian Community Psychiatric Services

Abstract: Despite the limitations of the study related to the short period considered, we believe this study offers some interesting information on the burden of schizophrenia, a disease for which its cost has received limited attention so far in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
3
16
0
5
Order By: Relevance
“…2.8 of all combined health service and community social care expenditures, and over 5 of all in-patient linked expenditure [2]. This consistent pattern of high levels of direct cost associated with schizophrenia is similar to that observed in other developed countries, including Germany [3,4,5,6].…”
supporting
confidence: 78%
“…2.8 of all combined health service and community social care expenditures, and over 5 of all in-patient linked expenditure [2]. This consistent pattern of high levels of direct cost associated with schizophrenia is similar to that observed in other developed countries, including Germany [3,4,5,6].…”
supporting
confidence: 78%
“…Questa patologia psichiatrica è caratterizzata dalla presenza di sintomi psicotici, comportamento catatonico, riduzione dei contatti sociali e appiattimento affettivo. I pazienti schizofrenici presentano severi problemi di disabilità che provocano gravi ripercussioni nella sfera sociale, professionale e familiare [9][10][11], contraddistinti da frequenti episodi psicotici che a volte possono essere accompagnati da deliri e allucinazioni, aggressività, violenze su persone o cose e tentativi di suicidio.…”
Section: * Pharmes Studi DI Valutazione Economica Milanounclassified
“…Of this total cost, 53.2% were direct costs of treating schizophrenia and 46.8% were indirect costs due to lost productivity, incarceration and family care giving [19]. Meanwhile, COI studies have been conducted in many countries and information on total and average individual direct and indirect costs are available [20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Cost Of Schizophreniamentioning
confidence: 99%
“…While in the USA, in 1990 the proportion of drug costs on total direct costs was assessed at 2.3% [19]. Studies conducted during the mid-1990s found higher proportions of 6-10% [23,46,48], and in more recent studies the proportion was found to be between 10 and 16% [31,38,47]. The increase of the proportion of drug costs on total costs results from a general increase in antipsychotic drug use and change of prescription practice which is characterized by a decreasing use of first-generation conventional antipsychotics and an increasing use of second-generation atypical compounds [49][50][51][52][53][54].…”
Section: Direct Costs Assessmentmentioning
confidence: 99%
See 1 more Smart Citation